PENGELOLAAN PENDAPATAN DAN BELANJA RUMAH TANGGA PEMULUNG - M.E Perseveranda; Lawalu, Emiliana Martuti; Indrawati, Agnes Susanti; Pongge, Maria Imakulata; Ketmoen, Adrianus; Masri, Marius; Dima, Enike Tje Yustin; Leki, Salomon (LPPM Universitas Bina Bangsa, 2024)
Scavengers are a group of urban poor who work in the informal sector, with their main activity being the collection of used goods every day to sell in order to meet their living needs. This condition places the management of income and expenditure as a key factor in efforts to improve the welfare of scavenger households. The income earned by scavengers at the Alak Landfill includes cash as well as goods and services. From an economic perspective, cash income contributes to an increase in household spending budgets, while income in the form of goods and services helps reduce expenses, which indirectly expands their spending capacity. A deep understanding of the dynamics of the lives of scavenger households in Alak District is crucial in designing effective strategies to improve their income and welfare. Therefore, a comprehensive study is needed to identify the challenges faced by scavenger families and find practical solutions, so that it can serve as the foundation for the implementation of this service program at TPAS Alak, Kupang City. The service team at TPAS Alak held a socialization event related to financial management, focusing on two main aspects. First, providing financial education to scavengers to help them manage household income and expenses more efficiently. Second, providing access to financial counseling services that support scavengers in budgeting and overseeing various financial challenges. This program has a positive impact on the scavengers at the Alak Landfill Site, including improved welfare for them and their families, increased access to financial services, as well as enhanced economic independence and a better understanding of financial management.